Including a Symposium on Robert Heilbroner At 100 - Fiorito, Luca (Research in the History of Economic Thought and Methodology Ser., 2019)
This volume features a symposium celebrating the centenary of the influential economist and historian of economic thought Robert Heilbroner. The volume also features original general-research contributions, as well as a new discovery of material from the archives of Richard A. Musgrave.